Reconciling temperature-dependent factors affecting mass transport losses in polymer electrolyte membrane electrolyzers. (1st June 2020) - Lee, ChungHyuk; Lee, Jason K.; George, Michael G.; Fahy, Kieran F.; LaManna, Jacob M.; Baltic, Elias; Hussey, Daniel S.; Jacobson, David L.; Bazylak, Aimy
Graphical abstract: Highlights: Increasing the temperature leads to reduced mass transport overpotential. Increasing the temperature leads to increased anode oxygen gas. Increasing the temperature leads to enhanced reactant distribution in the anode. Decreasing water viscosity dominates the resulting mass transport overpotential. Abstract: In this work, we investigated the impact of temperature on two-phase transport in low temperature (LT)-polymer electrolyte membrane (PEM) electrolyzer anode flow channels via in operando neutron imaging and observed a decrease in mass transport overpotential with increasing temperature. We observed an increase in anode oxygen gas content with increasing temperature, which was counterintuitive to the trends in mass transport overpotential. We attributed this counterintuitive decrease in mass transport overpotential to the enhanced reactant distribution in the flow channels as a result of the temperature increase, determined via a one-dimensional analytical model. We further determined that gas accumulation and fluid property changes are competing temperature-dependent contributors to mass transport overpotential; however, liquid water viscosity changes led to the dominant enhancement of reactant water distributions in the anode. We present this temperature-dependent mass transport overpotential as a great opportunity for further increasing the voltage efficiency of PEM electrolyzers.